2017
DOI: 10.1111/jpn.12604
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protein fermentation and carbohydrate source on in vitro methane production

Abstract: Incubations were carried out with batch cultures of ruminal micro-organisms from sheep to analyse the influence of the N source on in vitro CH production. The two substrates were mixtures of maize starch and cellulose in proportions of 75:25 and 25:75 (STAR and CEL substrates, respectively), and the three nitrogen (N) sources were ammonia (NH Cl), casein (CA) and isolated soya bean protein (SP). Five isonitrogenous treatments were made by replacing non-protein-N (NPN) with CA or SP at levels of 0 (NPN), 50 (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…These authors also noticed that using different blanks (with or without enzymes added) for correcting gas production values altered the differences between experimental treatments and changed the interpretation of results. The increased total VFA production and the shifts in VFA profile observed in our study when the blanks were pre-digested also indicated a fermentation of enzymes, as the amino acids resulting from proteolysis can be deaminated and the generated carbon skeletons be fermented to VFA (Van Soest, 1994;Vanegas et al, 2017). The greater isovalerate proportions detected in the predigested blanks are consistent with this hypothesis, because this VFA generally arise from the fermentation of leucine (Wallace and Cotta, 1988).…”
Section: Modification Of the In Vitro Fermentation Methodologysupporting
confidence: 83%
“…These authors also noticed that using different blanks (with or without enzymes added) for correcting gas production values altered the differences between experimental treatments and changed the interpretation of results. The increased total VFA production and the shifts in VFA profile observed in our study when the blanks were pre-digested also indicated a fermentation of enzymes, as the amino acids resulting from proteolysis can be deaminated and the generated carbon skeletons be fermented to VFA (Van Soest, 1994;Vanegas et al, 2017). The greater isovalerate proportions detected in the predigested blanks are consistent with this hypothesis, because this VFA generally arise from the fermentation of leucine (Wallace and Cotta, 1988).…”
Section: Modification Of the In Vitro Fermentation Methodologysupporting
confidence: 83%
“…The experimental diets were formulated to contain a high proportion of cereal grains (62.2 and 45.2% for low‐ and high‐protein diets respectively) because Vanegas, González, et al. () observed that the contribution of protein fermentation to CH 4 production was greater with a rapidly fermentable substrate (starch) than with a slowly fermentable substrate (cellulose). Diets with two different CP levels were formulated to analyse the possible interaction between treatment and CP level.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary characteristics are one of the most important factors influencing CH 4 production, and it is well known that diets rich in structural carbohydrates yield higher CH 4 emissions compared with those high in non‐structural carbohydrates (Kumar et al., ). A recent in vitro study (Vanegas, González, & Carro, ) showed the generation of CH 4 from pure protein fermentation and that the response in CH 4 production to protein supply differed with the basal substrate, being higher for a rapidly fermented substrate than for a slowly fermented one. In addition, the protection of sunflower protein against ruminal degradation by a combined treatment of malic acid and heat resulted in a reduction of in vitro CH 4 production that was attributed to reduced protein degradation (Vanegas, Carro, Alvir, & González, ; Vanegas, González, Alvir, & Carro, ).…”
Section: Introductionmentioning
confidence: 99%
“…and the generated carbon skeletons be fermented to VFA (Van Soest, 1994;Vanegas et al, 2017). The greater isovalerate proportions detected in the pre-digested blanks are consistent with this hypothesis, as these VFA generally arise from the fermentation of leucine (Wallace and Cotta, 1988).…”
Section: Discussionmentioning
confidence: 73%